Immunity to Ichthyophthirius infections in fish: A synopsis - Dickerson, H.W.; Findly, R.C. (Developmental and comparative immunology, 2014)
•Review of the immune response of fish to infection by Ichthyophthirius multifiliis.•Innate and adaptive immune responses are described.•Mucosal immune responses are addressed.•A model describing the immune response is presented. Ichthyophthirius multifiliis is a ciliated protozoan parasite that infects freshwater fish. It has been the subject of both applied and basic research for over 100years, which can be attributed to its world-wide distribution and its significant economic impact on both food and aquarium fish production. I. multifiliis serves as a model for studies in fish on innate and acquired immunity, as well as on mucosal immunity. Although an obligate parasite, I. multifiliis is relatively easily passaged from infected to naïve fish in laboratory aquaria, and is easily observed and manipulated under laboratory conditions. It parasitizes the epithelia of the skin and gills, which facilitates in vivo experimentation and quantification of challenge. This review provides a description of both mucosal and systemic innate and adaptive immune responses to parasite infection, a synopsis of host–parasite immunobiology, vaccine research, and suggested areas for future research to address critical remaining questions. Studies in carp and rainbow trout have shown that extensive tissue damage occurs when the parasite invades the epithelia of the skin and gills and substantial focal and systemic inflammatory responses are elicited by the innate immune response. The adaptive immune response is initiated when phagocytic cells are activated by antigens released by the parasite. It is not known whether activated T and B cells proliferate locally in the skin and gills following infection or migrate to these sites from the spleen or anterior kidney. I. multifiliis infection elicits both mucosal and systemic antibody production. Fish that survive I. multifiliis infection acquire protective immunity. Memory B cells provide long-term humoral memory. This suggests that protective vaccines are theoretically possible, and substantial efforts have been made toward developing vaccines in various fish species. Exposure of fish to controlled surface infections or by intracoelomic injection of live theronts provides protection. Vaccination with purified immobilization antigens, which are GPI-anchored membrane proteins, also provides protection under laboratory conditions and immobilization antigens are currently the most promising candidates for subunit vaccines against I. multifiliis.